MEDIA INTERAKTIF PENGENALAN BAHASA ISYARAT BISINDO - Bayu Ramadhani Fajri; Agariadne Dwinggo Samala; Fadhli Ranuharja (Universitas Negeri Padang, 2020)
Sign language is the communication that used by the deaf people. Sign language is also a form of accessibility for deaf people to be able to socialize with people around them. Deaf socialization with normal people in the society is not optimal because most of the people does not yet know sign language. Based on these problems, this study aims to develop an interactive media introduction to BISINDO sign language based on augmented reality for the community in supporting a society that is more inclusive of the deaf. This study uses a Research and Development (R&D) approach. The sample in this study was deaf people who participated in the Gerkatin Padang community, and people from various professions in the city of Padang. The data collection technique was carried out using a questionnaire and a focused group discussion technique. Based on the results of the collection of 100 respondents' perceptions data from the public towards sign language obtained: 1) the level of getting to know the community towards sign language is still low at 57%, 2) the level of skills using sign language is still low at 83%, 3) the importance level of sign language according the community is 81%, 4) The level of community needs to learn Sign Language is obtained by 88%, and 5) The level of selection of the right media for learning Sign Language, 74% of respondents choose media in the form of a smartphone application. The validity of the interactive media prototype introduction BISINDO sign language developed in terms of substance that is the suitability of sign language in the application obtained a validator rating of 89.33%, then in terms of the media obtained a validator value of 89.67%. It can be concluded that the interactive media prototype in the form of a smartphone application that was developed very well in terms of substance and media so that it is very feasible or valid to be used in the introduction of BISINDO sign language.